Linguistic And Cultural Issues In Video Report Texts By Eesp Internship Students - Alfriani Ndandara; Ifoni Ludji; Naniani N. Benu; Aelsthri Ndandara (Journal of Language and Applied Linguistics, 2026)
The research investigates cultural and linguistic challenges in translating Indonesian video report texts into English and examines the strategies employed to address these challenges. Adopting a qualitative descriptive design, the research draws on paired source texts and their English translations, which were analyzed using content analysis to identify recurrent cultural and linguistic issues as well as the translation strategies applied. The findings indicate that cultural challenges primarily involve the incomplete transfer of cultural references, values, and local practices, resulting in aspects of cultural identity and social meaning not being fully represented in the target texts. Linguistic issues include non-idiomatic sentence structures, inappropriate lexical selection, and grammatical inconsistencies. The analysis further reveals that translators predominantly rely on literal translation, limited cultural adaptation, and generalization strategies, which often overlook contextual and pragmatic nuances in the target language. These findings underscore the necessity of cultural competence, advanced linguistic proficiency, and more context-sensitive translation strategies to ensure accurate and effective communication for international audiences. This study is limited to texts produced by students, so the findings may not apply to professional translators. The study contributes both theoretically by extending the understanding of cultural and linguistic issues in multimedia translation and practically by providing insights for improving translation pedagogy and translator training in educational contexts.